2019
DOI: 10.1155/2019/9208734
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Titanium Oxide Layers Modified with Gold, Silver, and Copper Nanoparticles

Abstract: Titanium(IV) oxide is commonly used in photocatalysis. However, it has some drawbacks, e.g., a high rate of electron-hole recombination and a wide bandgap. In here, the surface of anodic titanium(IV) oxide (ATO) was modified with metal nanoparticles (gold, silver, and copper) in order to enhance its photoelectrochemical (PEC) and photocatalytic (PC) properties. SEM analysis revealed that Au, Ag, and Cu nanoparticles obtained on an ATO surface by chemical methods had an average diameter of 50 ± 10 nm, 30 ± 6 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…A significant improvement in absorption due to surface plasmon resonance between 500 and 600 nm was achieved as shown, resulting from the interaction of the metal particles with the incident light. The improvement of the photocatalyst efficiency by the inclusion of metallic particles such as silver could be confirmed by Fermi energy levels which were displaced at values close to the bottom of the conduction band; the accumulation of electrons influences the plasmon absorption band, which can improve the photocatalytic activity of a material in the visible region [20,23] our results indicates that the bandwidth of the titanium modified with silver was 2.9 EV.…”
Section: Doping Of the Catalyst And Characterization Of Tio 2 /Agsupporting
confidence: 52%
See 2 more Smart Citations
“…A significant improvement in absorption due to surface plasmon resonance between 500 and 600 nm was achieved as shown, resulting from the interaction of the metal particles with the incident light. The improvement of the photocatalyst efficiency by the inclusion of metallic particles such as silver could be confirmed by Fermi energy levels which were displaced at values close to the bottom of the conduction band; the accumulation of electrons influences the plasmon absorption band, which can improve the photocatalytic activity of a material in the visible region [20,23] our results indicates that the bandwidth of the titanium modified with silver was 2.9 EV.…”
Section: Doping Of the Catalyst And Characterization Of Tio 2 /Agsupporting
confidence: 52%
“…A significant improvement in absorption due to surface plasmon resonance between 500 and 600 nm was achieved as shown, resulting from the interaction of the metal particles with the incident light. The improvement of the photocatalyst efficiency by the inclusion of metallic particles such as silver could be confirmed by Fermi energy levels which were displaced at values close to the bottom of the conduction band; the accumulation of electrons influences the plasmon absorption band, which can improve the photocatalytic activity of a material in the visible region [20,23] our results indicates that the bandwidth of the titanium modified with silver was 2.9 EV. The results of X-ray diffraction (DRX), as well as the results of scanning electron microscopy (SEM) and those of the analysis of the chemical composition of the catalyst (SEM-EDS) have been published in a previous article [24]; they indicated that the actual percentage of deposited silver was 3.4% and that there was no evidence of alteration in the composition of the crystalline phase of the catalyst significantly due to the inclusion of metallic silver.…”
Section: Doping Of the Catalyst And Characterization Of Tio2/agsupporting
confidence: 52%
See 1 more Smart Citation
“…The significantly faster effect of this component composition of thin films as well as overcoming the resistance of the highly adaptive Pseudomonas DSM50026 can be explained by the structure of the nanocomposite films. The doping of TiO 2 with Ag and Cu nanoparticles improved the photoresponse and photocurrent density of TiO 2 into the visible light region [21][22][23]. Other authors proved the several mechanisms of action of silver [17,18] and copper nanoparticles [16,20,21,24].…”
Section: Discussionmentioning
confidence: 99%
“…The modified TNTs formed on Ti-based implants can reduce bacterial colonization on their surfaces accordingly. Alternatively, antibacterial CuNPs can be used to replace AgNPs for doping TNTs with improved biocompatibility [98,99]. CuNPs are less toxic than AgNPs to human and bovine mammary epithelial cells [344].…”
Section: Prospects and Challengesmentioning
confidence: 99%